From Policy to Polity: Can the EU’s special relations with its Neighbourhood be Decentred?” - Nicolaidis, K; Bechev, D (2010)
“From Policy to Polity: Can the EU’s special relations with its Neighbourhood be Decentred?” with Dimitar Bechev, Journal of Common Market Studies, June 2010